2020
DOI: 10.1093/cid/ciaa1785
|View full text |Cite
|
Sign up to set email alerts
|

Serologic Testing of US Blood Donations to Identify Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2)–Reactive Antibodies: December 2019–January 2020

Abstract: Background SARS-CoV-2, the virus that causes COVID-19 disease, was first identified in Wuhan, China in December 2019, with subsequent worldwide spread. The first U.S. cases were identified in January 2020. Methods To determine if SARS-CoV-2 reactive antibodies were present in sera prior to the first identified case in the U.S. on January 19, 2020, residual archived samples from 7,389 routine blood donations collected by the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
97
2
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(106 citation statements)
references
References 24 publications
5
97
2
2
Order By: Relevance
“…Our results are similar to other retrospective testing that focused on PCR-based detection of residual samples [4-6]. Evaluation of residual specimens using antibody tests is still an on-going effort and may lead to different data as better assays comes available [7].…”
Section: Discussionsupporting
confidence: 83%
“…Our results are similar to other retrospective testing that focused on PCR-based detection of residual samples [4-6]. Evaluation of residual specimens using antibody tests is still an on-going effort and may lead to different data as better assays comes available [7].…”
Section: Discussionsupporting
confidence: 83%
“…In fact, increasing number of reports in the literature are consistent with some antibodies to HCoV being crossreactive with the betacoronaviruses SARS-CoV-2 and SARS-CoV-1. [28][29][30][31][32] Interestingly, significant protein similarity between SARS-CoV-1, SARS-CoV-2, and other HCoV has been reported for N, including a highly conserved motif in the N-terminal (NT) half of the protein (FYYLGTGP) 33 and relevant immunodominant epitope regions. 24,34 Likewise, preexisting SARS-CoV-2-specific T cells have also been reported in »40%À60% of unexposed individuals and attributed to crossreactivity with HCoV previously encountered.…”
Section: Introductionmentioning
confidence: 99%
“…While these may diminish its usefulness as an approach for detecting ongoing infections, for which the reliability needs to be improved by adopting smarter testing strategies ( CDC, 2020f ) or combining with other testing methods ( Guo et al., 2020 ), the method itself serves a useful tool for conducting retrospective investigations on early infections and propagation of COVID-19, especially in the lack of pre-archived samples specifically fulfilling such a purpose. In fact, the usefulness of this approach was demonstrated in two recent serological surveys published in the interim during the review of this article, which showed real-life evidence that antibody testing of archived human blood donations can be a useful tool for identifying early infections of COVID-19 in the population before the first known local case of COVID-19 infection ( Apolone et al., 2020 ; Basavarain et al., 2020 ). These findings confirmed the earlier observation of SARS-CoV-2 antibodies in a small number of stored plasma samples ( n = 5) in Lombardy, Italy and the postulation that a prior unnoticed circulation of the virus had occurred in the area ( Percivalle et al., 2020 ).…”
Section: Using Stored Human Body Fluids and Biological Materials For mentioning
confidence: 91%